2020
DOI: 10.4149/bll_2020_107
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability features for different stress classification

Abstract: AIM: Autonomic nervous system (ANS) activities during different types of stress could affect the electrocardiogram (ECG) signal. This study aimed to recognize the types of stress by using different ECG signals in order to prevent its actual physiological effects on the heart signal. METHOD: The ECG signal recorded by portable wrist bracelets from 20 students in during seven phases which incorporated three different types of stress and four relaxation phases. After different forms of windowing the signal, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…There are numerous different methods reported in the stress detection literature for inducing stress. These include different arithmetic tasks [20,26,28,29,34], games/puzzles [25,30], exam-like conditions [14,16,19,31], and everyday situations such as driving [38,39] or work shifts [9,10,33]. However, not all of these are standardised and reliable stressors, only ad hoc methods designed and implemented by the researchers themselves, often without psychological expertise.…”
Section: State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations
“…There are numerous different methods reported in the stress detection literature for inducing stress. These include different arithmetic tasks [20,26,28,29,34], games/puzzles [25,30], exam-like conditions [14,16,19,31], and everyday situations such as driving [38,39] or work shifts [9,10,33]. However, not all of these are standardised and reliable stressors, only ad hoc methods designed and implemented by the researchers themselves, often without psychological expertise.…”
Section: State Of the Artmentioning
confidence: 99%
“…In comparison with the results of Ham et al [23], who have achieved 81-82% accuracy with non-overlapping 4-min-long time windows, we have achieved an accuracy of 86.67%, which could be increased to 94.60% by using overlapping time windows of the same length. Moridani et al [20] reported an F1 score of 97.9% for differentiating between cognitive stress and relaxation using 5-min-long measurements. Our results for overlapping 5-min-long time windows using time-domain and non-linear HRV features were quite similar, with an F1 score of 96.26%.…”
Section: Comparison To Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…HRV refers to the variation in the RR interval of the electrocardiogram, which indicates the instantaneous heart rate, and is affected by the balance between the sympathetic and parasympathetic nervous systems. The low-frequency/highfrequency ratio (LF/HF) obtained from the analysis of the HRV frequency is used as a surrogate parameter for sympathetic overactivity and is associated with stress load [31][32][33]. There are several reports on the validity of HRV in assessing stress levels [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%